BASIC CONCEPTS AND PRECONDITIONS FOR DENIAL OF GENOCIDE: CONTEMPORARY CHALLENGES FOR HUMAN RIGHTS - Oleshchenko, Veronika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the concept of genocide and the phenomenon of its denial, analysis of classifications and methods of denial of genocide. Research methods: general scientific and special legal methods of scientific knowledge are applied, in particular: system-structural method, observation method, generalization method, methods of analysis and synthesis. Results: the author concluded that the denial of genocide has four preconditions: 1) unwillingness to psychologically accept the brutality of crimes; 2) substitution or contradiction of historical facts; 3) political position of the government; 4) support of ideological "anti-democratic" movements. Discussion: the nature of the origin of genocide denial was analyzed and it was found that in most cases, according to research results, the political aspect of genocide denial prevails over the legal one, since the crime of genocide is committed by the government or the state, which greatly complicates the process of incrimination and prosecution, the result of which can become a geopolitical conflict. The author concludes that the above genocide denial has four roots: 1) unwillingness to psychologically accept the brutality of crimes; 2) substitution or contradiction of historical facts; 3) political position of the government; 4) support for ideological "anti-democratic" movements. He also emphasises that not only a more thorough interpretation of the concept of "genocide" and its consolidation in international legal documents will help to eradicate such crimes in the modern world. Also, a detailed analysis of the phenomenon of "genocide denial", i.e. where this ideology comes from and an understanding of why and for what purpose, will provide an important basis for arguments by lawyers and international organisations that firmly defend the position of human rights protection.